Metformin protects ovarian granulosa cells in chemotherapy-induced premature ovarian failure mice through AMPK/PPAR-γ/SIRT1 pathway - Yang, Yuxin; Tang, Xiangting; Yao, Ting; Zhang, Yiqing; Zhong, Yufei; Wu, Shuqing; Wang, Yurou; Pan, Zezheng (Scientific reports, 2024)
Premature ovarian failure (POF) caused by chemotherapy is a growing concern for female reproductive health. The use of metformin (MET), which has anti-oxidative and anti-inflammatory effects, in the treatment of POF damaged by chemotherapy drugs remains unclear. In this study, we investigated the impact of MET on POF caused by cyclophosphamide (CTX) combined with busulfan (BUS) and M1 macrophages using POF model mice and primary granule cells (GCs). Our findings demonstrate that intragastric administration of MET ameliorates ovarian damage and alleviates hormonal disruption in chemotherapy-induced POF mice. This effect is achieved through the reduction of inflammatory and oxidative stress-related harm. Additionally, MET significantly relieves abnormal inflammatory response, ROS accumulation, and senescence in primary GCs co-cultured with M1 macrophages. We also observed that this protective role of MET is closely associated with the AMPK/PPAR-γ/SIRT1 pathway in cell models. In conclusion, our results suggest that MET can protect against chemotherapy-induced ovarian injury by inducing the expression of the AMPK pathway while reducing oxidative damage and inflammation.